Tobacco smoking, chewing habits, alcohol drinking and the risk of head and neck cancer in Nepal. Issue 3 (27th December 2019) - Chang, Chun‐Pin; Siwakoti, Bhola; Sapkota, Amir; Gautam, Dej K.; Lee, Yuan‐Chin Amy; Monroe, Marcus; Hashibe, Mia
Abstract : Although tobacco smoking, pan chewing and alcohol drinking are important risk factors for head and neck cancer (HNC), the HNC risks conferred by products available in Nepal for these habits are unknown. We assessed the associations of tobacco smoking, chewing habits, and alcohol drinking with HNC risk in Nepal. A case–control study was conducted in Nepal with 549 incident HNC cases and 601 controls. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression adjusting for potential confounders. We observed increased HNC risk for tobacco smoking (OR: 1.54; 95% CI: 1.14, 2.06), chewing habits (OR: 2.39; 95% CI: 1.77, 3.23), and alcohol drinking (OR: 1.57; 95% CI: 1.14, 2.18). The population attributable fraction (PAF) was 24.3% for tobacco smoking, 39.9% for chewing habits and 23.0% for alcohol drinking. Tobacco smoking, chewing habits, and alcohol drinking might be responsible for 85.3% of HNC cases. Individuals who smoked tobacco, chewed products and drank alcohol had a 13‐fold increase in HNC risk (OR: 12.83; 95% CI: 6.91, 23.81) compared to individuals who did not have any of these habits. Both high frequency and long duration of these habits were strong risk factors for HNC among the Nepalese with clear dose–response trends. Preventive strategies against starting these habits and support for quitting these habits are necessary to decrease the incidence of HNC in Nepal. Abstract : What's new? Associations between head and neck cancer (HNC) risk and tobacco smoking, pan chewing, and alcohol use are well established. In Nepal, however, little is known about relationships between these behaviors and risk of developing HNC. In this case‐control study in Nepal, the authors observed increased HNC risks for tobacco smoking, chewing habits, and alcohol drinking. Individuals who engaged in all three behaviors were markedly affected, experiencing a 13‐fold increase in HNC risk compared to individuals who did not engage in any of these activities. The results highlight the impact of behavioral factors on HNC risk in Nepal.